PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA KOTA SIBOLGA - Wilbert Ramonray Butarbutar (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2019)
This article based on research aims to determine the process of public ordering street vendors conducted by the Civil Service Police Unit of the City of Sibolga. The root of the problem of the disorder of street vendors and the right solution to overcome the root of the problem. Data collection in this study uses a descriptive method with an inductive approach. The source of the author’s data is the Civil Service Police Unit of Sibolga City, street vendors, and the community of Sibolga City. The instruments used are interviews, observation, and documentation. The data analysis technique used is the problem tree analysis technique. The results showed that the process of public ordering street vendors in the protocol road area by the Sibolga City Civil Service Police Unit had not been carried out optimally. This is due to the lack of personel in the Sibolga City Civil Service Police Unit compared to the large number of points of violation by street vendors in Sibolga City, as well as the lack of agricultural products in Sibolga City which includes the coastal areas of North Sumatera. Keywords: Street Vendors; Public Order; Public Space